Differential Expression and Evolution of the Arabidopsis CYP86A Subfamily - Duan, Hui (American Society of Plant Biologists, 2005)
Some members of the Arabidopsis (Arabidopsis thaliana) CYP86A and CYP94B cytochrome P450 monooxygenase subfamilies, which share some sequence homology with the animal and fungal fatty acid hydroxylases, have been functionally defined as fatty acid ω-hydroxylases. With these activities, these and other fatty acid hydroxylases have potential roles in the synthesis of cutin, production of signaling molecules, and prevention of accumulation of toxic levels of free fatty acids. The constitutive and stress-inducible patterns of the five Arabidopsis CYP86A subfamily members have been defined in 7-d-old seedlings and 1-month-old plant tissues grown under normal conditions, and 7-d-old seedlings treated with different hormones (indole-3-acetic acid, abscisic acid, gibberellin, methyl jasmonic acid, brassinosteroid, salicylic acid), chemicals (clofibrate, 1-aminocyclopropane-1 carboxylic acid), or environmental stresses (cold, wounding, drought, mannitol, etiolation). Very distinct expression patterns exist for each of these fatty acid hydroxylases under normal growth conditions and in response to environmental and chemical stresses. Analysis of the promoter sequences for each of these genes with their expression patterns has highlighted a number of elements in current databases that potentially correlate with the responses of individual genes.